The Effect of Employee Perception on the Liberation of Personal Income Tax during the Covid 19 Period at PT. Philips Seafood Indonesia In Barru Regency - Andi Nurhidayah Supratman (Pustaka Digital Indonesia, 2023)
This study aims to determine the effect of employee perceptions on the exemption of personal income tax during the Covid 19 period at PT. Philips Seafood Indonesia In Barru Regency. The primary data in this study is the employee's perception of the exemption of personal income tax during the Covid-19 period, which is measured by using a response to a coiusine that uses ordinal measurements with a 5-point Likert scale. The statistical method used to test the hypothesis is simple linear regression analysis with the help of SPSS The results of this study indicate that the Effect of Employee Perception on the Liberation of Personal Income Tax during the Covid 19 Period at PT. Philips Seafood Indonesia In Barru Regency. The resultis a positive effect, based on the significance value, if the singnificance value is < 0,05 means positive effect